The usage of live streaming in affecting customer purchase intention - Chen, Bonian (2023)
The purpose of this study was to explore the factors that influence customers' purchase intention in live streaming, including social media celebrity, informativeness and user-generated content. Customer satisfaction will then be explored as a mediator.